CD247, a Potential T Cell–Derived Disease Severity and Prognostic Biomarker in Patients With Idiopathic Pulmonary Fibrosis - Li, Yupeng; Chen, Shibin; Li, Xincheng; Wang, Xue; Li, Huiwen; Ning, Shangwei; Chen, Hong (Frontiers in Immunology, 2021)
Background: Idiopathic pulmonary fibrosis (IPF) has high mortality worldwide. CD247 molecule (CD247, as known as T-cell surface glycoprotein CD3 zeta chain) has been reported as a susceptibility locus in systemic sclerosis, but its correlation with IPF remains unclear. Methods: Datasets were acquired by researching the Gene Expression Omnibus (GEO). CD247 were identified as the hub gene associated with percent predicted diffusion capacity of the lung for carbon monoxide (Dlco% predicted) and prognosis according to Pearson correlation, logistic regression, survival analysis. Results: CD247 is significantly down-regulated in patients with IPF compared with controls both in blood and lung tissue samples. Moreover, CD247 is significantly positively associated with Dlco% predicted in blood and lung tissue samples. Patients with low-expression CD247 had shorter transplant-free survival (TFS) time and more composite end point events (CEP, death or decline in FVC >10% over six months period) compared with patients with high-expression CD247 (blood). And, in the follow-up 1st, 3th, 6th, 12th months, low expression of CD247 was still the risk factor of CEP in the GSE93606 dataset (blood). Thirteen genes were found to interact with CD247 according to protein-protein interaction network, and the 14 genes including CD247 were associated with the functions of T cell and natural killer (NK) cell such as PD-L1 expression and PD-1 checkpoint pathway and NK cell mediated cytotoxicity et al. Furthermore, we also found that low expression of CD247 might be associated with lower activity of TIL (tumor infiltrates lymphocytes), check point, cytolytic activity, and higher activity of macrophages and neutrophils. Conclusion: These results imply that CD247 may be a potential T cell-derived disease severity and prognostic biomarker for IPF.